A Study On Japanese Mingei’s Birth In Taisho Era And Alienation In Showa Era - Wu Yeyan (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Yanagi Sōetsu put forward the word "Mingei (Folk Craft)" in 1925 and jointly published the "Purport Book on the Establishment of Japan Mingei Museum" with Tomimoto Kenkichi, Kawai Kanjiro, and Hamada Shoji the following year, so as to launch Japan’s "Mingei movement". Some scholars have noticed that during World War II, Mingei was related to "life culture" with fascist ideology, and there was a historical phenomenon that Mingei served politics. This paper attempts to interpret the first-hand texts of Yanagi Sōetsu, Kunio Kishida, and Kiyoshi Miki, discuss how Mingei with a "healthy" original intention came into being, and how it gradually became a tool for Japanese fascist aggression and expansion. Mingei originated in the period of "Taisho Democracy," with a strong left-wing flavor in Japanese history. It contains a beautiful vision of making society "healthy". It has gained influence with the support of elites, and the Mingei movement has progressed well in rural and urban society. Later, Mingei gradually attracted the attention of the Showa fascist government and was absorbed by the concept of "life culture" advocated by the new system in 1940, which was alienated and became a tool for the mobilization of the Japanese fascist war.
Keywords: Japanese folk craft